Banking on the poor: unleashing the benefits of microfinance - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
This policy brief is designed to help policymakers and practitioners understand the financial services needed by the poor. It is framed within lessons learned from a five-year IFPRI research program that examined, among other issues, the roles government should play in providing financial services to meet the needs of the poor. Insights presented here are based on a series of detailed household surveys conducted in nine countries of Africa and Asia: Bangladesh, Cameroon, China, Egypt, Ghana, Madagascar, Malawi, Nepal, and Pakistan.... [The brief asks us to consider these questions:] What kinds of financial services do the poor value? What economic activities are the poor engaged in, and what implications does this have for the type of services to be provided? What are existing sources of financial services, and how do the poor use them? What combination of financial instruments—credit, savings, insurance — are best developed, given specific demand from different types of clients? Do delivery systems (credit union, village banking, group-based lending) take into account the prevailing socioeconomic environments or local organizational systems? What unconventional methods do the poor use to secure loans? Can these collateral substitutes be used within a more formalized banking system? In the lending or granting of public resources, are incentives in place to encourage competitive, sustainable, efficient, and entrepreneurial microfinance institutions? Are regulations in place that govern mutually supportive transactions between the clients (borrowers) and institutions (lenders), such as deposit insurance and contract enforcement? Are prudential regulations, such as accounting practices and reporting requirements, balanced so that they ensure sustainability, good management, and accountability of microfinance institutions without stifling innovation? Would the introduction or expansion of microfinance services in a region be one of the most socially cost-effective ways to alleviate poverty there, given the state of infrastructure and markets, the availability of services, and the existence of other antipoverty and development programs in the region?" -- Text